2016
DOI: 10.1097/rlu.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Renographic Demonstration of Desmoid Tumor-Ureteral Fistula

Abstract: A 20-year-old woman with Gardner syndrome and intra-abdominal desmoid tumors presented with increasing abdominal pain. CT demonstrated a new area of central hypodensity in a presumed desmoid tumor, compressing the left ureter. Findings were suspicious for abscess or fistula to the ureter. Subsequent 99mTc-MAG3 renogram demonstrated persistent extraureteral radiotracer activity in the region of the tumor, confirming a desmoid tumor-ureteral fistula. Desmoid tumors are benign but locally aggressive fibrous neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“… 17 , 18 Approximately 25% of the lesions are painless and may be identified via bone and radiological screening. 1 , 19 Consistent with the literature, the most common causes of admission among our patients were pain and pathological fractures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 17 , 18 Approximately 25% of the lesions are painless and may be identified via bone and radiological screening. 1 , 19 Consistent with the literature, the most common causes of admission among our patients were pain and pathological fractures.…”
Section: Discussionsupporting
confidence: 90%
“…Skeletal metastases account for 70% to 80% of all malignant bone lesions. 1 Skeletal metastases are more commonly found than primary bone tumors. Approximately one-third of each diagnosed extraskeletal carcinoma results in skeletal metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…This tumor has infiltrative features and can result in urinary tract obstruction, and occasionally, an abscess or fistula (1). However, ureteral fistulas caused by desmoid tumors are rarely reported (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies have reported the utility of renal DTPA scintigraphy for detecting abnormal formation of the urinary tract (3,5).…”
Section: Introductionmentioning
confidence: 99%